Total bacterial counting and the response to treatment of bacterial vaginosis with metronidazole - Luchiari, Heloise Ranucci [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Objective: To evaluate if the total bacterial count of vaginal samples with bacterial vaginosis assessed by flow cytometry influences the response to treatment with metronidazol. Methods: In this cross-sectional study, 273 low-risk reproductive aged women were enrolled. Vaginal samples were taken to evaluate the pattern of vaginal flora according to Nugent’s criteria, as well as the presence of trichomoniasis and candidosis. Cases identified of bacterial vaginosis were treated with metronidazole and controlled after 45 days. Cervical infection by Chlamydia trachomatis and Neisseria gonorrhoeae were also assessed. Flow cytometry for total bacterial counting was performed in propidium iodide stained cervicovaginal samples, using fluorescent beads at a known concentration. Non-parametric Mann-Whitney test was used to compare total bacterial count between groups of interest, at p<0.05. Results: From the total of 273 women enrolled, 50 were excluded as they presented at least one of the infections investigated. Bacterial vaginosis was detected in 79 women (35.4%), of which 33 (41.8%) returned for re-evaluation after treatment, being 21 cases successfully treated and 12 with persistent abnormal vaginal flora. Flow cytometric data showed that total bacterial counting does not differ between normal flora and bacterial vaginosis samples (p=0.14). Also, no difference was found between the cases of treated and persistent bacterial vaginosis (p=0.48). Conclusion: Total bacterial counting does not influence the response to metronidazole treatment of bacterial vaginosis
Keywords: Bacterioses; Vaginose bacteriana; Citometria de fluxo